MODERN SYNTAXIC COMPETENCE OF BASIC SCHOOL STUDENTS AND ITS ROLE IN THE FORMATION OF A NEW PERSONALITY OF A STUDENTS (EDUCATION IN THE 21ST CENTURY, 2023)
The article deals with a modern approach to the study of sentence syntax in the intermediate school. The method of projects is relevant at the present stage of studying syntax. The essence of the project is to guide students to the formation of a problem, the so-called key question. Thematic issues are often difficult to understand and contradictory. In this way, it leads students to reflect, search, and explore. Pupils learn to think outside the frame, have improved learning outcomes, and the creativity of each child also increases. When using the project method, it is important to: formulate hypotheses, use research methods, analyze the data obtained.To enhance the educational and cognitive activity of students in the classroom, a cognitive methodology was introduced, aimed at the intellectual development of students; modeling of educational situations that induce various types of speech activity. The goal of the cognitive methodology is the mastery of concepts by students - the deep meanings of the detailed content structures of the text, the formation of skills for adequate perception of textual information and the creation of their own (oral and written) statements, increasing interest in the language, etc.
Keywords: Keywords: scientific approach to the study of syntax in intermediate school, open language space, binary lesson, cases, syntactic competence, experience of introspection, cognitive technique.